2014
DOI: 10.1159/000359958
|View full text |Cite
|
Sign up to set email alerts
|

Characterising Haemodynamic Stress during Haemodialysis Using the Extrema Points Analysis Model

Abstract: Background and Aims: It is becoming recognised that the process of haemodialysis (HD) itself induces circulatory stress that could be implicated in the observed higher rate of end-organ damage. We aimed to study the haemodynamic performance during HD using the extrema points (EP) analysis model, and to examine the determinants of the model and its relation to circulatory stress. Methods: 63 incident HD patients were studied. Mean arterial blood pressure (MAP) EP frequencies and baroreflex sensitivity during HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…25 We then demonstrated that this hemodynamic behavior is exacerbated by the circulatory stress of HD as the MAP extrema points frequencies continue to rise throughout the dialysis session to peak during the third quarter of the session. 49 Furthermore, in a randomized controlled trial, we found that cooling the dialysate could have a protective effect on brain white matter by altering this hemodynamic behavior. 16 In that trial, higher frequencies of MAP extrema points were associated with measures of acute damage in brain white matter.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…25 We then demonstrated that this hemodynamic behavior is exacerbated by the circulatory stress of HD as the MAP extrema points frequencies continue to rise throughout the dialysis session to peak during the third quarter of the session. 49 Furthermore, in a randomized controlled trial, we found that cooling the dialysate could have a protective effect on brain white matter by altering this hemodynamic behavior. 16 In that trial, higher frequencies of MAP extrema points were associated with measures of acute damage in brain white matter.…”
Section: Discussionmentioning
confidence: 90%
“…We have previously demonstrated that in the resting state, extrema points frequencies of MAP seem to be much higher in HD than a normal control . We then demonstrated that this hemodynamic behavior is exacerbated by the circulatory stress of HD as the MAP extrema points frequencies continue to rise throughout the dialysis session to peak during the third quarter of the session . Furthermore, in a randomized controlled trial, we found that cooling the dialysate could have a protective effect on brain white matter by altering this hemodynamic behavior .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We conducted ECG tests on each patient 10 minutes before HD and 15 minutes before the end of HD (at peak stress [ 9 ]). The recordings were taken using a 12-lead machine (MAC 1200, GE) at 10mm/mv and 25mm/s.…”
Section: Methodsmentioning
confidence: 99%